Up the garden path - Garden art for everyone! - Eplényi, Anna (4D Journal of Landscape Architecture and Garden Art, 2013)
A few years ago I visited the souvenir shop of the gardens of Versailles, and among the millions of books propagating garden art and garden history, there was one that caught my eye. It was a large activity booklet for kids – typically French in its elegance, modernity and creativity – a collection of the most important moments in garden art history, transforming the genre's playfulness and gestures into drawingart-exercises suitable for deepening even the younger children's awareness for this versatile art form.
Keywords: garden art; children